A practical guide to characterizing irradiated nuclear fuels using FIB tomography. (July 2022) - McKinney, Casey; Smith, Charlyne; Helmreich, Grant; Gerczak, Tyler; Aitkaliyeva, Assel
Abstract: Focused ion beam (FIB) tomography with combined electron backscatter diffraction (EBSD) and energy dispersive x-ray spectroscopy (EDS) is a technique capable of statistically characterizing the microstructure and spatial compositional variation of nuclear fuel in three-dimensions (3D). The 3D visualization from FIB tomography provides a comprehensive picture of the interconnected microstructural and compositional features that can impact fuel performance. While these features are often characterized with surface examination, the complexity and relationship of fission products and grain boundary networks may not fully be captured by these 2D methods. This work presents a practical guide to FIB tomography that is tailored to nuclear fuel characterization. The steps used to collect and process the data are provided along with the scripts used to process the data. Additionally, suggestions for future characterization efforts utilizing this approach are given. Highlights: Fiji, MATLAB, and Dream.3D are used to analyze 3D FIB tomography data. Multimodal data analysis performed on stacks of SE micrographs, EDS, and EBSD. The method is tailored to irradiated nuclear fuel and associated challenges. The scripts used to analyze the fuel are included and referenced.